PERFECTION CLAUSES, SUMMARY EXECUTION (PARATE EXECUTIE) CLAUSES, FORFEITURE CLAUSES (PACTA COMMISSORIA) AND CONDITIONAL SALES IN PLEDGE AGREEMENTS AND NOTARIAL BONDS  THE POSITION CLARIFIED - Lee Steyn (Obiter, 2022)
A number of recent cases in various divisions of the High Court and in the Supreme Court of Appeal have concerned clauses, in notarial bonds and in agreements for cession of rights in securitatem debiti, which permit the creditor, upon default of the debtor, without recourse to a court, either to take possession of, to retain, to acquire or to sell the property provided as security for the performance of the debt. The decisions reflect a measure of controversy surrounding the validity of such clauses in light of the rule against self-help and section 34 of the Constitution (Act 108 of 1996) which provides that everyone has the right to have any dispute that can be resolved by the application of law decided in a fair public hearing before a court. Other considerations which have been taken into account have been freedom of contract, the principle of pacta sunt servanda and whether such terms are contra bonos mores. The validity of such clauses has significance, particularly, for grantors of credit, who frequently rely upon them to provide security for their debtors‟ obligations, and, consequently, for commerce generally.In the most recent case, Bock v Dubororo Investments (Pty) Ltd (2004 2 SA 242 (SCA)), notably, the Supreme Court of Appeal overruled the decision in Findevco (Pty) Ltd v Faceformat SA (Pty) Ltd (2001 1 SA 251 (E)), in which it was held that summary execution was unconstitutional, and, consequently, we have greater clarity in relation to this issue. It is useful, I submit, to analyse the decision in Bock v Dubororo Investments (Pty) Ltd (supra) in the context of the applicable general legal principles and relevant precedent, to gain perspective on the current legal position.